Monitoring the phase evolution of Cu(In, Ga)Se2 by different Se flux via in‐situ XRD. Issue 8 (26th February 2016) - Zahedi‐Azad, Setareh; Jarzembowski, Enrico; Hartnauer, Stefan; Wägele, Leonard; Greiner, Dieter; Scheer, Roland
Abstract: Through in‐situ X‐ray diffraction, we examined the phase evolution of Cu(In, Ga)Se2 films deposited by three stage co‐evaporation with regard to Se flux and substrate temperature. The deposition method is based on the sequence of Cu‐poor/Cu‐rich/Cu‐poor, which is beneficial for improving the crystal quality as well as the conversi‐on efficiency. We find that while the Se flux during the first stage determines the final orientation, the substrate temperature moderates the degree of the preferred orientation. The orientation of the intermediate Cu2 Se phase follows the preferred orientation of the CIGSe film, indicating an epitaxial relationship between the two phases.